Occurrence of the "Peaking Effect" Corresponding to the "Highest Range of Effective Intensities" exhibited by Bacteriorhodopsin (bR) - Carboxymethylcellulose (CMC) Biosensor upon Illumination - P, Vengadesh; Abdul Majid, Wan Haliza; Shanmugam S, Anandan; K.S, Low (Malaysian Journal of Science, 2008)
Photo-electrical characterization works were carried out to understand the basic functionality of the novel bacteriorhodopsin (bR) - Carboxymethylcellulose (CMC) photosensor proposed and fabricated earlier. A single-pixel sensor was fabricated and its photoresponse towards light intensities and thermal variations studied. The occurrence of the "peaking effect" corresponding to a certain "highest range of effective intensities" upon light illumination was also observed and discussed.